Analisis Pemahaman Aparatur Nagari Tentang Pajak Penghasilan (PPH) Dan Pajak Pertambahan Nilai (PPN): Studi Deskriptif pada Kabupaten Pasaman Barat - Mayar Afriyenti; Charoline Cheisviyanny; Herlina Helmy (Wahana Riset Akuntansi, 2017)
Law No. 6 Year 2014 about Desa (District) states that districts are given a great opportunity to manage their own governances as well as the implementation of development to improve the welfare and quality of life of district communities. Therefore, the district government should be able to apply the principle of accountability in its governance, where all the end of district governance activities must be accountable to the district community in accordance with the provisions. District Finance Management is regulated in the Peraturan Menteri Dalam Negeri (Minister of Home Affairs Regulation) No. 113 Year 2014. One of the obligations of the District is to collect and deposit collected tax to the state. Since it is still relatively a new regulation, then the treasurers’ understanding of the tax obligations is still uneven, such as Income Tax and Value Added Tax (VAT), so the treasurers need to be trained. The training activity was held for two days at the Office of the Badan Pengelolaan Keuangan Daerah (Regional Financial Management Agency) of Pasaman Barat Regency. The participants are the treasurer and staff of 19 nagari with 25 participants. At the end of training, participants were given a quizionnaire with 25 questions about tax. The result showed that there were 20 participants whose level of understanding has reached more than 50%, or it can be concluded also that 80% of participants have gained increased understanding and knowledge about Income tax and Value Added Tax (VAT).Keywords: : treasurer, income tax, value added tax